PENINGKATAN PEREKONOMIAN DESA MELALUI PERAN BUMDES ASSINGKERUKENGNGE PERSPEKTIF SIYASAH SYAR’IYYAH - Ismail, Andi Reni Anggraeni; Anis, Muhammad (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
Village Owned Enterprises (BUMDes) are business entities whose management is managed directly by the government and village communities, which aims to improve the welfare of the people, in order to improve the economy and the original income of the village (PAD). This study aims to determine the extent of the role of BUMDes Assingkerukengnge Mallari Village, Bone Regency in improving the village economy based on the perspective of siyasah syar'iyyah. The research methods used are field research with syar'i, juridical, and sociological approaches. The results showed that BUMDes Assingkerukengnge Mallari Village has played a very good role in order to increase the Village's Original Income and has contributed to the economic improvement of the people of Mallari Village. The existence of BUMDes is considered very helpful, especially capital loan facilities prepared with relatively easy conditions, so the role of BUMDes Assingkerukengnge is very helpful in efforts to improve the economy of rural communities.